Processos de tomada da palavra em LI: da língua objeto à sujeição à língua - Ângelo, Rogério de Castro (2020)
In this work, we set out to research the representations of the students of a Language Center (CENID) of a Federal Institute in relation to the process of teaching and learning English, more specifically in relation to the process of taking the word for oral production in English. Some of the questions we sought to answer throughout this dissertation were: What are the discourses of CENID students about their subjectification processes in the English language? Why do English language students often feel they are not authorized to speak English? The general objective of this research was to investigate the processes of subjectification in the English language by CENID students. Regarding the constitution of the corpus, we used the AREDA proposal, proposed by Serrani-Infante (1998a) both as a method for collecting testimonies and regarding the Discourse Analysis constructs that support it. For the analysis of the corpus, we articulated a dialogue between Discourse Analysis (DA) of French tradition as practiced in Brazil (GADET; PÊCHEUX, 2004; PÊCHEUX, 1993, 1997, 2015), Applied Linguistics (AL) (FABRICIO, 2006; MOITA LOPES, 1998, 2006; PENNYCOOK, 1998, 2001, 2006, 2007; RAJAGOPALAN, 2003, 2006) and decolonial thought (LANDER, 2000; MALDONADO-TORRES, 2007; MIGNOLO, 2003). From the analysis of the testimonies of the research participants, two different, but intertwined, configurations were configured in the relationship between the learning subjects and the English language, a rational and an affective assemblage, and the oral practices work as a destabilizing element in relation to the attempts to control the language.